Entre o cachimbo e a fumaça: um estudo das memórias na cultura material da Jurema no Terreiro de Umbanda Ogum Beira Mar - Almeida, Carla Maria de (2021)
Jurema comprises an Afro-Amerindian religion, widely practiced in the Northeast, especially in Paraíba, but also in other regions of Brazil and has already reached other countries, like the European continent. Like other religions and cultural manifestations, it has a range of objects, including ornaments, musical instruments and other sacred things that make up the religious scene, which, in addition to being used in the performance of the rite, have historical and memorial values. Therefore, I seek to understand the memories built about Jurema through the constant information in the material culture and in the narratives of the most experienced faithful in the religious context. Material culture is understood as a document, whose contained information makes it possible to evoke memories about Jurema. Therefore, I performed participant observation, with emphasis on the ethnographic approach, understanding religion as a mesh of meanings that must be analyzed here in the light of semiotics. For the elaboration of the research, the Terreiro de Umbanda Ogum Beira Mar, located in João Pessoa, capital of the state of Paraíba, was observed. The terreiro was selected according to its relevance to religion, constituting references to a place of memory and a temple whose senior leadership had a unique role in the state's religious tradition. From the material religious culture, I sought to understand the sign diversity within Jurema, the information produced, its symbolic, historical and memorial aspects. Having said that, the study proposes, based on its insertion in the field of Information Science, to reflect on the object from the intersection of information, dissonances and constancies in relation to the information and memory of Jurema in Paraíba. The material cultures reflected are for collective and individual use, their reflection points to the way in which juremeiras and juremeiros conceive sacred objects, as holders of memory and science, which indicate characteristic aspects of knowledge involving religion. The analysis opposed classical studies on objects, overturning the colonizing view as a religiosity endowed with poor material culture. Material culture, added to narrated memories, constitute relevant sources, since, due to their uniqueness, they not only subsidize new research, but expand horizons in memory and culture studies in the field of Information Science.